Bibliometric Review of the Impact of International Financial Reporting Standards (IFRS) on Financial Statement Quality - Loso Judijanto; Nuniek Yuniarti Ningsih Renggaala (Westscience Press, 2024)
This bibliometric analysis investigates the impact of International Financial Reporting Standards (IFRS) on the quality of financial statements from 2000 to 2024. Utilizing data from academic publications, the study maps the evolution, key themes, and collaborative networks in IFRS research globally. Publication trends indicate a significant increase in research, particularly following major financial upheavals, highlighting the growing importance of standardized financial reporting. Country collaboration analysis demonstrates a widespread academic partnership across continents, emphasizing a unified approach to enhance financial transparency. Thematic investigations reveal core topics centered around earnings quality, audit quality, and fair value, alongside emerging interests in sustainable development and technological integration. The findings illustrate the substantial contributions of IFRS to financial reporting quality, the challenges of universal application across diverse regulatory landscapes, and the evolving nature of financial disclosure standards in response to new economic and technological developments.